The Burden of Liver Disease in Human Immunodeficiency Virus-Infected Patients - Puoti, Massimo; Moioli, Maria Cristina; Travi, Giovanna; Rossotti, Roberto (Seminars in Liver Disease, 2012)
Introduction of effective combined antiretroviral therapy has made human immunodeficiency virus (HIV) infection a chronic illness. Substantial reductions in the number of acquired immunodeficiency syndrome- (AIDS-) related deaths have been accompanied by an increase in liver-related morbidity and mortality. Liver diseases rank in the first three most-common causes of death in HIV-infected persons. Mortality is mainly due to cirrhosis and hepatocellular carcinoma induced by hepatitis C virus and hepatitis B virus coinfection. However, antiretroviral drugs toxicity also plays a role. Nonalcoholic fatty liver disease is a common cause of liver injury as well. Nevertheless, alcohol consumption probably plays a pivotal role. Noncirrhotic portal hypertension, an uncommon condition observed in less than 1% of patients, is increasingly described. Finally, acute hepatitis A virus (HAV) and acute and even chronic hepatitis E virus infection have also been reported as causes of liver damage in HIV. Anti-HAV vaccination is thus recommended in persons at risk living with HIV.
Keywords: human immunodeficiency virus; hepatitis C virus; nonalcoholic fatty liver disease; alcoholic hepatitis; liver-related mortality; cirrhosis; noncirrhotic portal hypertension